Effect of accounting information system quality on decision-making success and non-financial performance: does non-financial information quality matter? - Ngoc Tran Thanh Thuy (Cogent Business & Management)
This study aims to investigate the significance of accounting information system (AIS) quality in improving decision-making success (DMS) and non-financial performance (NFP) in the emerging economy. Additionally, the study delves into the mediating impact of non-financial information quality on the relationship between AIS quality, DMS, and NFP. This research emphasizes 306 non-financial companies in Vietnam. Primary data is acquired through a questionnaire survey administered to managers, chief accountants, heads of departments, and the board of directors of enterprises. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method is adopted to test the proposed model. The findings indicate that the quality of AIS and non-financial information significantly influences the overall success of decision-making and NFP. The results also validate that DMS plays a mediating role in the correlation between the quality of non-financial information and NFP. Eventually, the non-financial information quality and DMS are serial mediators that connect AIS quality and NFP. This study represents an inaugural attempt that utilizes the lenses of stakeholder, decision usefulness, and behavioral management theories to examine the relationship among AIS quality, non-financial information quality, DMS, and NFP in Southeast Asia. Hence, this study offers insightful implications for practitioners, managers, and policymakers in evaluating the impact of AIS and non-financial information quality on enhancing DMS and NFP in businesses.